Optimization of moist-heat and dry-heat treatment for the production of stabilized brown rice using box-behnken design - Palomo, Alex M.; Capanzana, Mario V.; Diaz, Dahlia A.; Garcia, Rosemarie G. (2020)
This study aims to optimize the processing parameters of combined moist- and dry-heat treatment to stabilize brown rice. The processing parameters including moist-heat treatment (MHT) time, dry-heat treatment (DHT) temperature, and DHT time were modeled using the Box-Behnken design. The optimum processing condition was verified by actual experimental runs and shelf-life study. The responses evaluated were free fatty acid (FFA) content, peroxide value (PV), and sensory properties of brown rice samples. The results showed that all processing parameters significantly affected the FFA content. MHT time has a significant effect on PV and off-odor, while DHT time affected the acceptability of texture and taste of brown rice. Some interaction effects among the processing parameters were also found significant. The optimum processing parameters were 75 min MHT time, 65 °C DHT temperature, and 70 min DHT time. The actual values of responses from actual experimental runs were in close agreement with the predicted values of the models. Treated brown rice samples have significantly lower FFA than control samples during storage. Decreased sensory acceptability of odor of treated brown rice samples was observed during longer storage time. (Author's abstract)